Challenges and Prescriptions for Homeless Drug Users’ Social Reintegration; An Experience of Partnerships Between Iran and Europe NGOs - Moghanibashi-Mansourieh, Amir (Journal of drug issues, 2024)
The research addressed challenges and prescriptions for reintegration of homeless people who use drugs. Data were collected through conducting semi-structured interviews. Twenty-nine participants were recruited. The primary codes were extracted and divided into two main categories of challenges and prescriptions; the former included becoming homeless after a long term recovery, workplace stigma, service users’ different cultural backgrounds, dismissing the 12-Step Program, message fatigue, negative effect of relapse on groups and cyberspace overuse; and the latter included connection by hook or by crook, abstinence-harm reduction orientation, organizational service collection, pushing boundaries of interventions, and expanding services umbrella.